Clinical Study on Efficiency of Using Traditional Direct Bonding or OrthGuide Computer-Aided Indirect Bonding in Orthodontic Patients. (29th September 2022) - Wang, Min; Shi, Xing; Cheng, Wei-Pu; Ma, Fei-Hu; Cheng, Si-Miao; Kang, Xuan
Abstract : Objective . This study aims to clinically investigate and compare the therapeutic effects and treatment cycle between traditional direct bonding and OrthGuide computer-aided indirect bonding in orthodontic treatment. Methods . Forty patients treated at the Department of Orthodontics, Beijing Rytime Dental Hospital between July 1, 2016, and December 31, 2019, were included. The patients were divided into a control group (n = 20, traditional direct bonding) and a test group (n = 20, OrthGuide computer-aided indirect bonding). The American Board of Orthodontics (ABO) measurement was performed on patients using Uceph cephalometric analysis software to compare intragroup and intergroup differences, and the treatment cycles of all patients were recorded. Results . After treatment, U1-NA (mm), ∠U1-SN (°), LL-EP (mm), and UL-EP (mm) in the control group were significantly lower than before treatment, and there was no significant difference in other ABO measurement indexes, while the test group showed no marked difference in all ABO measurements between pre- and posttreatment. Further, intergroup comparison showed no significant difference in ABO measurements in pre- and posttreatment between the two groups. The test group had a shorter treatment cycle than the control group, with an average treatment cycle of 21.20 ± 7.14 months in the control group and 17.17 ± 4.16 months in the test group. Conclusion . There was no significant difference in the therapeutic effects between the direct and indirect bonding techniques. However, OrthGuide computer-assisted indirect bonding demonstrated a significantly shorter treatment cycle and might be more efficient than traditional direct bonding.